The First Step of Introducing Risk Management for Prepossessing SLAs - Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Int. Conf. on Services Computing (SCC))

Reformulating XPath queries and XSLT queries on XSLT views - Groppe, Sven; Böttcher, Stefan; Birkenheuer, Georg; Höing, André (Data & Knowledge Engineering)

Risk Aware Migrations for Prepossessing SLAs - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Light Simulation in a Distributed Driving Simulator - Lietsch, Stefan; Zabel, Henning; Berssenbruegge, Jan; Wittenberg, Veit; Eikermann, Martin (Proc. Int. Symp. on Visual Computing (ISVC))

First Steps of a Monitoring Framework to Empower Risk Assessment on Grids - Lerch, Nicolas; Nitsche, Holger; Voss, Kerstin; Hovestadt, Matthias (Proc. Cracow Grid Workshop (CGW))

On Similarities of Grid Resources for Identifying Potential Migration Targets - Birkenheuer, Georg; Döhre, Sven; Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Cracow Grid Workshop (CGW))

Using WS-Agreement for Risk Management in the Grid - Birkenheuer, Georg; Djemame, Karim; Gourlay, Iain; Kao, Odej; Padgett, James; Voß, Kerstin (Proc. WS-Agreement Workshop (Open Grid Forum 18))

Adsorption of phenylglycine on copper: Density functional calculations - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Experimental and theoretical evidence for a hydrogen stabilizedc(2×2)reconstruction of the P-rich InP(001) surface - Letzig, T.; Willig, F.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Adsorption of water on chlorine-terminated Si(111) from first principles: Substrate-induced ordering versus intermolecular interactions - Biering, S.; Hermann, A.; Schmidt, Wolf Gero (Physical Review B)

Strongly bonded water monomers on the ice Ih basal plane: Density-functional calculations - Thierfelder, C.; Hermann, A.; Schwerdtfeger, P.; Schmidt, Wolf Gero (Physical Review B)

Tight-binding model for semiconductor quantum dots with a wurtzite crystal structure: From one-particle properties to Coulomb correlations and optical spectra - Schulz, S.; Schumacher, Stefan; Czycholl, G. (Physical Review B)

SLA-aware Job Migration in Grid Environments - Heine, Felix; Hovestadt, Matthias; Kao, Odej; Keller, Axel (Grid Computing: New Frontiers of High Performance Computing)
Grid Computing promises an efficient sharing of world-wide distributed resources, ranging from hardware, software, expert knowledge to special I/O devices. However, although the main Grid mechanisms are already developed or are currently addressed by tremendous research effort, the Grid environment still suffers from a low acceptance in different user communities. Beside difficulties regarding an intuitive and comfortable resource access, various problems related to the reliability and the Quality-of-Service while using the Grid exist. Users should be able to rely, that their jobs will have certain priority at the remote Grid site and that they will be finished upon the agreed time regardless of any provider problems. Therefore, QoS issues have to be considered in the Grid middleware but also in the local resource management systems at the Grid sites. However, most of the currently used resource management systems are not suitable for SLAs, as they do not support resource reservation and do not offer mechanisms for job checkpointing/migration respectively. The latter are mandatory for Grid providers as rescue anchor in case of system failures or system overload. This paper focuses on SLA-aware job migration and presents a work, which is being performed in the EU supported project HPC4U.

A Quality-of-Service Architecture for Future Grid Computing Applications. - Burchard, Lars-Olof; Heine, Felix; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Linnert, Barry (Proc. IEEE Int. Parallel & Distributed Processing Symposium (IPDPS))
The next generation grid applications demand grid middleware for a flexible negotiation mechanism supporting various ways of quality-of-service (QoS) guarantees. In this context, a QoS guarantee covers simultaneous allocations of various kinds of different resources, such as processor runtime, storage capacity, or network bandwidth, which are specified in the form of service level agreements (SLA). Currently, a gap exists between the capabilities of grid middleware and the underlying resource management systems concerning their support for QoS and SLA negotiation. In this paper we present an approach which closes this gap. Introducing the architecture of the virtual resource manager, we highlight its main QoS management features like run-time responsibility, co-allocation, and fault tolerance.

CoLoS - A System for Device Unaware and Position Dependent Communication Based on the Session Initiation Protocol - Lietsch, Stefan; Kao, Odej (Proc. Intelligence in Communication Systems (INTELLCOMM))

PIRANHA – Hunter of Idle Resources - Birkenheuer, Georg; Hagelweide, Wilke; Hagemeier, Björn; Japs, Viktor; Keller, Matthias; Mayr, Nikolas; Meyer, Jan; Schumacher, Tobias; Voß, Kerstin; Zajac, Markus (Proc. GI Informatiktage)

Polariton propagation in shallow-confinement heterostructures: Microscopic theory and experiment showing the breakdown of the dead-layer concept - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Rückmann, H. I.; Gutowski, J.; Gust, A.; Alexe, G.; Hommel, D. (Physical Review B)

Coherent propagation of polaritons in semiconductor heterostructures: Nonlinear pulse transmission in theory and experiment - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Wischmeier, L.; Rückmann, I.; Voss, T.; Gutowski, J.; Gust, A.; Hommel, D. (Physical Review B)

SLA-aware Job Migration in Grid Environments - Kao, Odej; Hovestadt, Matthias; Keller, Axel (Proc. Advanced Research Workshop on High Perfomance Computing: Technology and Applications)

An Architecture for SLA-aware Resource Management - Burchard, Lars-Olof; Heiss, Hans-Ulrich; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Linnert, Barry (Proceedings of the GI-Meeting on Operating Systems)